2017
DOI: 10.1007/s41111-017-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

South Africa in the Twenty-First Century: Governance Challenges in the Struggle for Social Equity and Economic Growth

Abstract: Since the advent of democracy in 1994, South Africa has undergone an extensive process of state reform aimed at overcoming the legacy of Apartheid and at building a more egalitarian social and political order. Whilst progress has been made in reforming the state infrastructure, the pursuit of an inconsistent economic growth path has meant that inequality and poverty remain serious challenges to the social order. The inability of oversight institutions to control powerful political interest groups, furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Norman‐Major (2011, 2022) expands the 3Es to include engagement , which we can also consider as having policy engagement elements, citizen participation, and collaborative public service to ensure relevance, cultural competence, and accountability; empathy , which looks into political neutrality; collective support for welfare systems; and ethics, loyalty to public interest, democratic participation, and access to information. Adequate case studies have demonstrated how African governments are dealing with efforts to entrench these Es to create a vibrant and democratic public service delivery (Ayisi et al., 2022; Onyango, 2023c; Tapscott, 2017).…”
Section: Literature Review: African Public Administration and Its Dem...mentioning
confidence: 99%
“…Norman‐Major (2011, 2022) expands the 3Es to include engagement , which we can also consider as having policy engagement elements, citizen participation, and collaborative public service to ensure relevance, cultural competence, and accountability; empathy , which looks into political neutrality; collective support for welfare systems; and ethics, loyalty to public interest, democratic participation, and access to information. Adequate case studies have demonstrated how African governments are dealing with efforts to entrench these Es to create a vibrant and democratic public service delivery (Ayisi et al., 2022; Onyango, 2023c; Tapscott, 2017).…”
Section: Literature Review: African Public Administration and Its Dem...mentioning
confidence: 99%
“…Political and administrative systems in the BRICS countries, as indicated, are very different from each other (Barabashev & Klimenko, 2017;Jing, 2017;Mathur & Mathur, 2017;Puppim de Oliveira, 2017;Tapscott, 2017). Box 1 provides a summary of the different intergovernmental relations systems in the BRICS and their varied responses to COVID-19.…”
Section: Intergovernmental Relations and Covid-19 In The Bricsmentioning
confidence: 99%
“…Since the post-apartheid era, the South African government attempted to develop and initiate various policies focused on transforming the country's agricultural sector, however, up to date; results prove to be relatively inconsistent (Tapscott, 2017). One can argue that the ultimate role of any government should be to bolster its nation with resources focused on creating nextgeneration entrepreneurs, ensure food safety, encourage jobcreation, economic development, improve financing structures, advance education and training, and to eliminate inequality among nationals throughout (Tapscott, 2017). Disappointingly, a variety of discriminative irregularities in current government practices and policies will continue limiting the vast potential of both existing and new entrants wanting to achieve growth in South Africa's agricultural sector (Steyn and Jackson, 2015).…”
Section: Government Supportmentioning
confidence: 99%
“…In the agricultural sector, entrepreneurs often face various uncertainties and disruptive elements that can occur at any time; thus, a strategized business plan remains an element that can keep things together in the event when it seems that intended plans unexpectedly go astray (Honig and Karlsson, 2004). Honig and Karlsson (2004) state that a business plan can be divided into segments defining strategy, operations, financial budgeting, and forecasting; however, statistics prove that a broad description of management and a high-quality executive summary remain the two most important areas (Becherer and Helms, 2009;Tapscott, 2017). With the current government, political, and economic challenges agricultural entrepreneurs in South Africa face, it is evident that a solidified business plan remains an applied strategy in the weapon-armoury of any successful entrepreneur (Becherer and Helms, 2009).…”
Section: Business Planmentioning
confidence: 99%